Cardiorespiratory and muscular fitness associations with older adolescent cognitive control - Tatsuya T. Shigeta; Angus A. Leahy; Jordan J. Smith; Narelle Eather; David R. Lubans; Charles H. Hillman (Elsevier, 2021)
Background: Participation in physical activity supports greater cardiorespiratory fitness (CRF), a correlate of cognitive control. However, the relationship between muscular fitness (MF) and cognitive control is less clear. The present study investigated the differential relationship of CRF and MF with cognitive control in older adolescents. Methods: This cross-sectional study involved students (15-17 years old, n = 541, 43% female) from 20 secondary schools who completed tests of inhibition (modified flanker task), working memory (n-back task), CRF (Progressive Aerobic Cardiovascular Endurance Run), and MF (standing long jump and push-up test). Multilevel analyses tested the association between CRF or MF and cognitive outcomes while accounting for the influence of the other fitness variable and relevant demographic factors. Results: CRF predicted response accuracy during incongruent flanker trials, the condition requiring greater inhibition. For the working memory task, CRF predicted greater target accuracy and greater d' scores on the 1-back task, requiring lesser amounts of working memory. In the 2-back task, which requires greater amounts of working memory, CRF also predicted greater target and non-target accuracy and d' scores. Comparatively, MF did not predict any cognitive outcomes after adjustment for CRF. Conclusion: CRF was selectively related to better performance during task conditions that require greater amounts of inhibition and working memory. This finding suggests that CRF, but not MF, may benefit cognitive control in older adolescents. This selective influence of CRF on older adolescents' cognition highlights the value of aerobic physical activity.